病人自主性與家庭本位主義之間的張力: The Tension between the Patient’s Autonomy and Familism - LEI, Jin-cheng; XIE, Zhi-qing (International Journal of Chinese & Comparative Philosophy of Medicine, 2002)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 在中國幾千年小農經濟和傳統文化背景下，個人利益、個人權利一直被置於家庭之下，個人自主性被包含在家庭自主性之內，表現為一種家庭本位主義。源自西方歷史、文化的知情同意移植到中國後，受傳統文化概念的影響，中國人對知情同意的認知、理解以及實踐方式均不同於西方人。這種不同集中表現在人們對家屬同意權的認可。以個人本位主義為背景的病人自主性與中國文化中的家庭本位主義之間存在張力。對知情同意在不同文化環境中不同踐行方式，應以文化寬容主義的態度對待之。不同文化背景下的倫理觀念，不僅存在差異性，而且也存在可通約性和相容性。由於種種原因，家庭同意並不能等同於病人本人的意願。隨著全球化進程的加速和人們相互交往的密切，類似知情同意這樣一些原本屬於個人的自然權利，將會愈來愈多地為各國人民接受。我們應當在某些條件具備時，盡可能地將家屬同意限制在合理的範圍，讓病人更好地表達自己的意願。 Family has a long history. With China’s small-scale peasant economy and traditional cultural background for centuries, family has been the most basic unit of polity, economy, and socio-cultural life. Interests and rights of the individual are always placed below those of family; individual autonomy is often included in family autonomy. All this can be called familism. There are deeper and determining economic reasons for familism. The economy of the family is controlled by the head of the family or clan so that the individual usually has no independent economic measures to support his or her autonomous rights. Informed consent originated in the Western culture. The theoretical premise of informed consent is respect for the patient’s autonomy. The patient’s autonomy is closely related with individualism in the West. After informed consent is spread from the West to China, due to the influence of traditional Chinese culture, the Chinese perception, understanding, and practice of are different from those of the West. The difference mainly lies in Chinese familism. To focus on the autonomy of the family reflects the influence of traditional familism upon informed consent. As a result, there exits a tension between the patient’s autonomy based on individualism and familism in Chinese culture. Informed consent is not a culture issue, but it is closely related with cultural tradition. It is impossible to get away with cultural norms in the practice of informed consent. To different practicing methods of informed consent in different cultural contexts, the spirit of cultural tolerance is needed. In China, with the principle of cultural tolerance as a practical guidance, we should establish a set of procedure and ways of practicing informed consent with Chinese characteristics. Fundamentally, informed consent is to balance the unbalanced power between doctors and patients. According to the principle of cultural tolerance, the difference in the practice of informed consent at different cultural contexts should be tolerated so long as the basic purpose of informed consent is not violated. There exists a variety of cultural ideas among contemporary Chinese. The individual patient and his or her family are essential part of informed consent, with both having their rationality. Thus, we shouldn’t reject absolutely some methods. From the angle of historical development, it is worthwhile noticing the transformation from family determination to individual autonomy. National and cultural differences are integrating in the age of globalization. Since laws, ethics, and customs in different countries and cultures are mutually exchanging, we should promote to make the practice of informed consent to become similar. DOWNLOAD HISTORY | This article has been downloaded 35 times in Digital Commons before migrating into this platform.